A STUDY ON THE EFFECTIVENESS OF ANTIFUNGAL AGENTS ON COTTON FABRICS COLORED BY GAMBIR NATURAL DYES (UNCARIA GAMBIR) - Edia Rahayuningsih; Felix Arie Setiawan; Conny Julanda Ayanie; Ambrosius Aditya; Yosephine Intan Ayuningtyas (Universitas Muhammadiyah Jakarta, 2019)
The increasing interest in the use of natural dyes is not accompanied by sufficient information and method for the application due to broad natural dyes resources existence. Gambir (Uncaria gambir), one of promising favorable natural dyes, has been used as batik coloring for decades. However, the application of gambir extract as a textile colorant faces a severe problem to be encountered which is the microbial growth such as fungi, mold, and bacteria. This study proposed several antifungal agents to suppress the growth of the fungus such as chitosan, aloe vera, and formaldehyde. To conduct the fungus inhibition concentration of every antifungal agent, Aspergillus niger was introduced on the colored cloth medium with the addition of Potato Dextrose Broth (PDB) growth media. Three methods of antifungal addition during the coloring process were investigated namely pre-coloring, post-coloring, and mix coloring process. The growth of Aspergillus niger was observed and measured the diameter and thickness of the colony. One-way ANOVA was used to analyze the treatment significantly. The result showed that all concentration of chitosan and formaldehyde addition, significantly, could suppress the fungus growth. However, formaldehyde is a toxic ingredient and harmful to the environment which becomes a limitation in the application. Meanwhile, from the significance level, Aloe vera could not inhibit the Aspergillus niger growth with the addition of 2 and 5 g/L, but it could suppress the Aspergillus niger growth with the addition of 8 g/L. Furthermore, the optimum condition was observed on the addition of 5 g/L chitosan at post-coloring method because of the minimum growth area of the Aspergillus niger.